2023
DOI: 10.1021/acs.jmedchem.3c01238
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Lipid Signatures in COVID-19 Infection: Diagnostic and Therapeutic Solutions

Aishi Dasgupta,
Shon Gangai,
Rishikesh Narayan
et al.

Abstract: The COVID-19 pandemic ignited research centered around the identification of robust biomarkers and therapeutic targets. SARS-CoV-2, the virus responsible, hijacks the metabolic machinery of the host cells. It relies on lipids and lipoproteins of host cells for entry, trafficking, immune evasion, viral replication, and exocytosis. The infection causes host cell lipid metabolic remodelling. Targeting lipid-based processes is thus a promising strategy for countering COVID-19. Here, we review the role of lipids in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 251 publications
(405 reference statements)
0
2
0
Order By: Relevance
“…The SARS-CoV-2 is no exception. For example, studies have found that the plasma lipid spectrum of COVID-19 patients has signi cantly changed compared with that of healthy people (Dasgupta et al, 2023). Bis(monoacylglycero)phosphate (BMP), an uncommon endolysosomal phospholipid that controls the destiny of endocytosed molecules, is required for the maintenance of lipid storage capacity and transit in the body, as well as the ne-tuning of the plasma membrane cholesterol domain (Akgoc et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SARS-CoV-2 is no exception. For example, studies have found that the plasma lipid spectrum of COVID-19 patients has signi cantly changed compared with that of healthy people (Dasgupta et al, 2023). Bis(monoacylglycero)phosphate (BMP), an uncommon endolysosomal phospholipid that controls the destiny of endocytosed molecules, is required for the maintenance of lipid storage capacity and transit in the body, as well as the ne-tuning of the plasma membrane cholesterol domain (Akgoc et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were as follows: (1) had undergone lung operations that affect lung function, such as lung transplantation, lung resection, lung volume reduction, etc. ; (2) rely on mechanical ventilation to maintain lung function, such as ventilators;(3) complicated with chronic lung diseases that affect lung function, such as chronic obstructive pulmonary disease; (4) complicated with diseases that affect heart function, such as pulmonary hypertension, heart failure, peripheral vascular disease, bromyalgia, etc., with cardiac pacemakers; (5) complicated with serious underlying diseases that affect survival, including uncontrolled clinically signi cant heart, kidney, digestive, hematological, neuropsychiatric, immune, metabolic, malignant, and severe malnutrition; (6) resting heart rate > 120/min; (7) systolic blood pressure > 180mmHg, diastolic blood pressure > 100mmHg; (8) unstable angina pectoris or myocardial infarction in the past 1 month; (9) severe obesity(BMI > 30kg/m 2 ); (10) allergic constitution, allergic to the drug ingredients involved in the treatment plan; (11) Pregnant or lactating women (12) unable to complete the collection of curative effect evaluation indicators (13) unable to cooperate in mental state, suffering from mental illness, lack of self-control, and inability to express clearly (14) participating in other clinical trials (15) according to the judgment of the researchers, there will be patients who affect the evaluation of e cacy and safety, such as complication or poor compliance.…”
Section: Patients Selectionmentioning
confidence: 99%